Preparation of Linseed Oil-Filled Urea–Formaldehyde Microcapsules and Anti-Corrosion Performance of Self-Healing Epoxy Coatings on Low Carbon Steel Substrate - Mohd Fauzi Mamat; Muhammad Hairy Muhdar; Nur Nadirah Dollah; Mohammad Rhadhi Kamshah; Mohd Farizul Jaafar; Lailatul Harina Paijan; Mohd Basri Ali; Mohd Hadzley Abu Bakar (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
This investigation utilised the in-situ polymerisation method to generate urea-formaldehyde (UF) microcapsules that were filled with linseed oil. Microcapsules with a mean diameter of 20-200 μm were obtained. The self-healing coating was constructed by incorporating 7.5wt. % microcapsules into an epoxy matrix and subsequently applying it to the low carbon steel substrate. The impact of microcapsules on the coating properties was examined through an immersion test in a 3.5wt. % NaCl medium for 7, 14, 21, 28, and 35 days. Weight loss and corrosion rate measurements were taken to investigate the effect of embedded microcapsules on the anticorrosive properties of the self-healing coating. Based on visual inspection, mass loss, and corrosion rate results, the complete self-healing coating demonstrated superior anticorrosive properties to the epoxy coating without microcapsules. The scratched self-healing coating’s failure was investigated using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Overall, the results and tests showed that the self-healing coating is more corrosion-resistant than the coating without microcapsules.